Our Secret Powers Telepathy, Clairvoyance and Precognition: A Short History of (Nearly) Everything Paranormal by Terje G. Simonsen - Pilkington, Rosemarie (Journal of Scientific Exploration, 2019)
Terje G. Simonsen is a Norwegian journalist who has written a very readable, inexpensive overview of the psi field for the interested lay public. It is fairly comprehensive covering a wide swath of topics from anthropology and archeology through laboratory experimentation to consciousness studies, philosophy, and research on reincarnation. It also includes references and links for each chapter, and separate indexes for subjects and names. These are very useful for the reader who would like to follow up and learn more about the many subjects covered. The writing is clear, entertaining and at times delightfully droll. (Some examples from his section headings: “Indiana Schwartz and the Lost Treasures of Alexandria,” “Which is Further Away: York or New York?—Entanglement and Non-locality,” “Ian Stevenson: Reincarnation, Again, and Again and Again . . .”) He presents dry data in interesting and amusing ways and the book is sprinkled with lots of intriguing anecdotes.